Classroom behaviour a practical guide to effective teaching, behaviour management and colleague support - Rogers, Bill 1947- (Los Angeles SAGE, 2015)
"This book looks at the issues facing teachers working in today's classrooms. Describing real situations and dilemmas, Bill Rogers offers his advice on dealing with the challenges of the job, and how building a rapport with both students and colleagues can support good practice."--Back cover.
Machine generated contents note: 1.The dynamics of classroom behaviour -- 2.New class, new year: the establishment phase of behaviour management -- 3.The language of behaviour management and discipline -- 4.Effective teaching: fundamental understandings and skills -- 5.Management beyond the classroom: behaviour consequences -- 6.Challenging children and children with emotional and behavioural difficulties -- 7.Managing anger in ourselves and others -- 8.When things get difficult: hard class, hard times.
Includes bibliographical references and index.
Keywords: Classroom management; Behavior modification; Effective teaching; Teachers -- Professional relationships